Características de consumo de codeína y tramadol en pacientes hospitalizados en el servicio de medicina iii del Hospital Nacional Guillermo Almenara Irigoyen – EsSalud Lima 2007 - Hoyos Arteta, Ana Patricia (2008)
The present descriptive, transverse, and restrospective study, had as objective to determine the characteristics of consume of codeine and Tramadol in the Service of Hospitalization of Medicine the III of the National Hospital Guillermo Almenara Irigoyen of the city of Lima during the year 2007. The population in study was shaped by all the patients' computerized records that consumed Codeine and Tramadol in the Service of Medicine the III of the National Hospital Guillermo Almenara Irigoyen - Is A Health during the year 2007, where it was investigated: consume of Codeine and monthly and annual Tramadol expressed in daily definite dose (DDD) for 100 beds - days, monthly consumer expenditure, and minimization of costs. The consumption of Codeine and Tramadol in National Hospital Guillermo Almenara Irigoyen - Is A Health during the year 2007 it was 0.80 and 0.54 respectively, that generated an expense of S/.9337.9 for the Codeine and S/. 8966.45 for the Tramadol.